2013
DOI: 10.1111/jan.12230
|View full text |Cite
|
Sign up to set email alerts
|

Resource need and use of multiethnic caregivers of elders in their homes

Abstract: Aims To predict South Florida family care-givers’ need for and use of informal help or formal services; specifically, to explore the predictive power of variables suggested by the Caregiver Identity Theory and the literature and develop and test a structural model 0. Background In the USA, most of the care to older adults is given by family members. Care-givers make economic and social sacrifices that endanger their health. They feel burdened, if they receive no assistance with their tasks; however, services… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…Previous studies have indicated that most family caregivers underuse healthcare resources and may have limited access to them. Furthermore, they may have religious or cultural beliefs, guilt about needing help, or difficulties finding suitable resources that place barriers to the use of services that would otherwise decrease their burden and meet their needs (Friedemann, Newman, Buckwalter, & Montgomery, 2014;Kim, Cho, & Lee, 2013;Mauk, 2012;Montgomery & Kosloski, 2013). Rehabilitation nurses act as patient advocates and educators who work in partnerships with the client and family (caregivers) to foster and support the patient's active participation in determining healthcare decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that most family caregivers underuse healthcare resources and may have limited access to them. Furthermore, they may have religious or cultural beliefs, guilt about needing help, or difficulties finding suitable resources that place barriers to the use of services that would otherwise decrease their burden and meet their needs (Friedemann, Newman, Buckwalter, & Montgomery, 2014;Kim, Cho, & Lee, 2013;Mauk, 2012;Montgomery & Kosloski, 2013). Rehabilitation nurses act as patient advocates and educators who work in partnerships with the client and family (caregivers) to foster and support the patient's active participation in determining healthcare decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly 90% of all participants in the Hughes et al [ 6 ] study expressed at least one need that was left unmet by the current system. Friedemann et al [ 20 ] found that availability of resources was influenced by language barriers, resistance to use services due to cultural or emotional reasons, lack of eligibility, mistrust of services, or inability to afford them. Formal services are rarely used in minority populations despite the expression of greater need for formal support services than non-minority caregivers [ 8 ], perhaps due to strong preferences for home care for family members [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that caring for patients with chronic disease often makes caregivers feel physically and psychologically exhausted and leads to a more negative psychological impact on caregivers [8]. Friedemann et al also indicated that patients' functional limitations yielded the strongest predictive coefficients followed by caregiver stress [33]. In people with chronic illnesses, increased knowledge can reduce the negative psychological impact on the patients or caregivers, such as anxiety and depression, and can enhance care efficiency [9][11].…”
Section: Discussionmentioning
confidence: 99%